2022
DOI: 10.3390/jcm11030660
|View full text |Cite
|
Sign up to set email alerts
|

The Hamburg Spondylodiscitis Assessment Score (HSAS) for Immediate Evaluation of Mortality Risk on Hospital Admission

Abstract: (1) Background: Patients with spondylodiscitis often present with unspecific and heterogeneous symptoms that delay diagnosis and inevitable therapeutic steps leading to increased mortality rates of up to 27%. A rapid initial triage is essential to identify patients at risk for a complicative disease course. We therefore aimed to develop a risk assessment score using fast available parameters to predict in-hospital mortality of patients admitted with spondylodiscitis. (2) Methods: A retrospective data analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
3
11
1
Order By: Relevance
“…The diagnostic sensitivity of blood cultures in SD and ISEE patients varies widely from 30% to 78% according to previously published reports [12,16,17,[24][25][26][27][28][30][31][32][33][34][35][36][37][38][39][40]. However, a systematic review of 14 clinical retrospective studies found that blood cultures routinely obtained in 91% of cases had an average sensitivity of 58%, which is consistent with our results (57.2%) [16].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The diagnostic sensitivity of blood cultures in SD and ISEE patients varies widely from 30% to 78% according to previously published reports [12,16,17,[24][25][26][27][28][30][31][32][33][34][35][36][37][38][39][40]. However, a systematic review of 14 clinical retrospective studies found that blood cultures routinely obtained in 91% of cases had an average sensitivity of 58%, which is consistent with our results (57.2%) [16].…”
Section: Discussionsupporting
confidence: 92%
“…However, a systematic review of 14 clinical retrospective studies found that blood cultures routinely obtained in 91% of cases had an average sensitivity of 58%, which is consistent with our results (57.2%) [16]. The diagnostic sensitivity of image-guided biopsy ranges from 44.1% to 82.5% and can be increased by using different techniques such as X-ray or CT for sampling and different sites such as psoas, disc, or vertebral body [12,17,24,25,29,[36][37][38][39]. Consistent with this spectrum, we were able to detect a pathogen with CT-guided biopsies from psoas abscess in 55.7% of cases.…”
Section: Discussionsupporting
confidence: 88%
“…Evidence-based therapeutic concepts for infectious spondylodiscitis of the lumbar spine are still lacking (11). However, the latest publications discuss the rationale for using newly developed classification systems in improving the treatment of spondylodiscitis (12,13). CF-caused pyogenic spondylodiscitis is very rare, whereby reported cases predominantly occurred in high-risk patients, as did in our reported case, but contrary to our case, without previous instrumented lumbar fusion surgery (1-8).…”
Section: Discussionmentioning
confidence: 52%
“…Evidence-based therapeutic concepts for infectious spondylodiscitis of the lumbar spine are still lacking ( 11 ). However, the latest publications discuss the rationale for using newly developed classification systems in improving the treatment of spondylodiscitis ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a German group of researchers suggested a score for evaluation of mortality risk on hospital admission, the Hamburg Spondylodiscitis Assessment Score. 18 It takes age, C-reactive protein, kidney function, and pathogen into account. When retrospectively applying the score to our patients, the one who died was indeed classified as at a very high risk for mortality.…”
Section: Discussionmentioning
confidence: 99%